Basal dinosauriform and theropod dinosaurs from the mid–late Norian (Late Triassic) of Poland: implications for Triassic dinosaur evolution and distribution. (16th April 2014) - Niedźwiedzki, Grzegorz; Brusatte, Stephen L.; Sulej, Tomasz; Butler, Richard J.; Benson, Roger
Abstract The rise of dinosaurs during the Triassic is a widely studied evolutionary radiation, but there are still many unanswered questions about early dinosaur evolution and biogeography that are hampered by an unevenly sampled Late Triassic fossil record. Although very common in western North America and parts of South America, dinosaur (and more basal dinosauriform) remains are relatively rare in the Upper Triassic deposits of Europe, making any new discoveries critically important. One of the most diverse dinosauriform assemblages from Europe comes from the Poręba site in Poland, a recently described locality with exposures of the Zbąszynek Beds, which have a palynomorph assemblage characteristic for the mid–late Norian in the biostratigraphic schemes of the Germanic Basin. Using a synapomorphy‐based approach, we evaluate several isolated dinosauriform specimens from Poręba. This assemblage includes a silesaurid, a herrerasaurid and remains of another type of theropod (potentially a neotheropod). The Poręba herrerasaurid is the first record of this rare group of primitive dinosaurs from Europe and one of the youngest records worldwide, whereas the silesaurid is the youngest record of a silesaurid from Europe. These findings indicate that silesaurids persisted alongside true dinosaurs into the mid–late Norian of Europe and that silesaurid–herrerasaurid–neotheropod assemblages (which are also known from the Norian of North America, at low latitudes) were more widespread geographically and latitudinally than previously thought. Silesaurid–herrerasaurid–neotheropod assemblages may have been a common ecological structuring of dinosaurs during their early evolution, and their widespread distribution may indicate weak palaeolatitudinal controls on early dinosaur biogeography during the latest Triassic.